THE INFLUENCE OF ENDURANCE, AGILITY AND EYE, HAND AND FEET COORDINATION ON LEARNING OUTCOMES OF RHYTHMIC MOVEMENTS IN PHYSICAL EDUCATION - Rosniawati; Hernawan; Yusmawati (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Abstract the purpose of this study was to determine whether there is a direct influence between endurance (X1), agility (X2), and eye, hand and feet coordination (X3) on the learning outcomes of rhythmic motion (Y) in physical education. The research method used is a quantitative approach with test and non-test techniques, while the analysis technique uses a path analysis approach or path analysis. The rhythmic motion test instrument uses a test instrument that the researchers developed based on an instrument grid that refers to theoretical studies. To measure agility, the test that will be used is the shuttle run test. The coordination test uses the Hand and Foot Eye Coordination Test Instrument from Sridadi. The population in this study were all students of class VIII SMPN 1 Napabalano. Sampling was done by means of total sampling. The sample in this study was class VIII students of SMPN 1 Napabalano, totaling 116 students. Data analysis techniques were carried out through two stages of analysis, namely descriptive and inferential data analysis. Based on the results of data analysis and hypothesis testing from research data, the variables of endurance, agility, eye, hand and feet coordination have a significant effect on the learning outcomes of rhythmic motion for class VIII students of SMPN 1 Napabalano.